Remodelado estructural sináptico en un modelo experimental de depresión - Podestá, María Fernanda (2014)
Hippocampal plasticity has been proposed to be involved in the pathophysiology of depression. However, it is unknown to what extent these changes are associated with the despair behavior and the antidepressant effect. We studied hippocampal synaptic ultrastructure in animals exposed to the Learned Helplessness (LH) model of depression as well as the effect of chronic fluoxetine administration on synaptic remodeling. The LH paradigm induced a decrease in hippocampal PSA-NCAM levels together with the despair acquisition (day 4). Ultrastructural synaptic alterations developed later on, concomitantly with decreased NCAM levels while PSA-NCAM expression remained decreased (day 25). Synaptic remodeling seen in LH animals was similar to that induced in hippocampal neurons in culture by glutamate. Treatment with fluoxetine corrected LH behavior, prevented synaptic alterations, exacerbated the NCAM reduction and increased PSA-NCAM levels. Persistent PSA-NCAM decrease was found influoxetine-resistant animals. The intra-hippocampal administration of a functional PSA mimetic peptide improved LH behavior and prevented synaptic remodeling. These results indicate PSA-NCAM participation in the pharmacological action of fluoxetine. Together, PSA-NCAM emerges as a novel target for pharmacological treatment of this disease.